Critical discourse in fiction in Iraq - ولي فتاح حيدر يحيى (Al-Adab Journal, 2018)
If we look approaches monetary modernist; we will find it either focused on the form or sense, or they called to close the text at the expense of the recipient, or called to open the text and allow for freedom of reception, including those brokered between this and that, and during that were just variations on the approaches of during readings wide variety her; due Alttoralve hit Humanities particularly linguistics that fueled literary criticism. this study attempt to determine the level of critical discourse in the book (fiction in Iraq since World War II trends intellectual and values ​​of art); to show how close Obadh for approaches modernist cash that flowed into us in the early seventies of the last century.